PENGEMBANGAN BAHAN AJAR IPA BERBASIS PBL TERINTEGRASI STEM UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS PADA MATERI GERAK LURUS - Parno; Alifia Asterina Putri; Yessi Affriyenny (Jurnal Penelitian Multidisiplin Ilmu, 2023)
Teaching material is a learning media that can construct an independent learning strategy however there is a few development of learning media using a contextual problem, STEM training aspect, and applying independent learning strategy. The purpose of the research is to develop and test the eligibility of teaching material (IPA), problem-based learning integrated with STEM to enhance the critical thinking skill on uniform motion material for proper instruction. The research design utilized research and development (R&D) with a 4-D model (Four D) which is developed by Thiagarajan (1974). The research stages include four primary steps: (1) define, (2) design, (3) develop, and (4) disseminate. The results of validation expert presented the teaching material developed has an average feasibility percentage of 96% and media expert has indicated the average percentage eligibility of 90%. The readability results by teachers pointed out that teaching material has an average readability of 100% and readability results from 15 students have 100% average readability. Thus, it can be concluded that teaching material (IPA) based PBL-STEM has proper criteria to increase the critical thinking skill.